2018
DOI: 10.1002/cam4.1743
|View full text |Cite
|
Sign up to set email alerts
|

SNP interactions of PGC with its neighbor lncRNAs enhance the susceptibility to gastric cancer/atrophic gastritis and influence the expression of involved molecules

Abstract: Multidimensional interactions of multiple factors are more important in promoting cancer initiation. Gene‐gene interactions between protein‐coding genes have been paid great attention, while rare studies refer to the interactions between encoding and noncoding genes. Our research group previously found encoding gene PGC polymorphisms could affect the susceptibility to atrophic gastritis (AG) and gastric cancer (GC). Interestingly, several SNPs in long noncoding RNA (lncRNA) genes, just adjacent to PGC, were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It also has been reported that lncRNAs play an important role in the pathogenesis of GC ( Lin et al, 2014 ). According to studies on lncRNAs in GC and CAG, there is one report showing that single-nucleotide polymorphisms (SNPs) interact with PGC, a coding gene with its adjacent lncRNAs, which could affect a person’s susceptibility to GC and CAG ( Lv et al, 2018 ). In that study, 15 pairwise interacting PGC-lncRNA SNPs were found, in which five pairs were relevant to CAG risk.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been reported that lncRNAs play an important role in the pathogenesis of GC ( Lin et al, 2014 ). According to studies on lncRNAs in GC and CAG, there is one report showing that single-nucleotide polymorphisms (SNPs) interact with PGC, a coding gene with its adjacent lncRNAs, which could affect a person’s susceptibility to GC and CAG ( Lv et al, 2018 ). In that study, 15 pairwise interacting PGC-lncRNA SNPs were found, in which five pairs were relevant to CAG risk.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rs3807598, rs2067087, and rs17427960 polymorphisms may also be applied to predict CRC susceptibility in some specific populations, such as young people and individuals without smoking or drinking history. Furthermore, the role of one single factor on disease risk was limited and usually reported to be weak, but the combination of multiple factors may have stronger roles and markedly affect the susceptibility to cancer [40,41]. To identify some potential combination effects that cannot be revealed in univariate analyses, we evaluated the interactions between all the environmental factors and SNP genotypes, although only H. pylori infection was demonstrated to be associated with CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found that the serum expression level of lncRNAs adjacent to PGC could distinguish gastric cancer, atrophic gastritis and superficial gastritis [16]. In addition, Lv et al reported that 10 pairwise PGC-lncRNA single nucleotide polymorphisms (SNPs) were associated with gastric cancer risk, and might enhance the susceptibility to gastric cancer [17]. Several other studies focused on the miRNAs targeting PGC and their relationship with gastric cancer.…”
Section: Ivyspringmentioning
confidence: 99%